Cine Tauro: a lustful island in the chaos of lima. Subjects and heritage values around the modern object - Dordan Barboza, Katherine (2023)
The objective of this article is to present the development of the investigation of the case: “Cine Tauro: a lustful island in the chaos of Lima. Subjects and heritage values around the modern object”. The main objective of this research is to understand the reasons why the Taurus cinema, a representative project of the modernity of Peruvian architecture of the early 1960s, remained isolated, decadent and dying in the officially called monumental urban environment of the 20th century of the Fence of Lima.